(untitled) (Bangladesh Journal of Medical Science, 2021)
Kidney transplantation (KT) is currently the most realistic treatment option for patients with end-stage renal disease (ESRD) as it enables them to live longer and provides better quality of life post-transplantation. Before the 1960s, all these patients would die as there was no treatment available. It is the commonest solid organ transplantation carried out in the world at the moment. Organs are harvested from living or cadaveric donors, with living kidney donor organs generally functioning better and for longer periods of time compared to the latter. Issues surrounding organ transplantation in general and kidney transplantation in particular, are fraught with ethical dilemmas due to the shortage of organs, the logistics behind the acquisition of organs, use of living donors including minors and the black market that has sprouted thereof. Entwined in this quagmire are the legal, social and psychological consequences for the individuals involved and the society at large. It is further compounded by religious concerns, which have a significant influence on the society’s acceptance of the practice of organ donation. The practice of organ transplantation is generally accepted by most Islamic scholars as it is concordant to the objectives of Islamic Law (maqasid al Sharī’ah) which prioritize the preservation of human life. However, resistances do arise from some jurists and even physicians of the same Islamic faith despite a fatwas decreeing that organ and tissue transplantations are permissible in Islam under certain conditions. The take-up of organ-donation is still largely poor especially among Muslims. This article therefore hopes to explore the various moral and ethical issues surrounding KT as well as the Islamic viewpoints emanating from it. We hope that this knowledge and understanding will benefit both health-care personnel and the public in general. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.241-249